The Locating Chromatic Number of Pizza Graphs Containing a Single Path on the Outer Vertices - Irawan, Agus; Bachtiar, Nasrullah; Irfan, Miftahul; Ratam, Aldila Nur Indah Berliana; Marisa, M.; Azzanina, Nanda (Jurnal MSA ( Matematika dan Statistika serta Aplikasinya), 2025)
In graph theory, the locating chromatic number refers to the minimum number of colours required to colour the vertices of a graph such that each vertex is uniquely identifiable by its own colour and the colours of its neighbouring vertices. This concept is associated with graph coloring, which entails assigning colors to a graph's vertices in such a way that no two adjacent vertices have the same color. It determines the minimum number of colours necessary to produce a proper vertex colouring. This research focuses on determining the locating chromatic number of Pizza graphs containing a single path on the outer vertices.